The invisible leverage of the top 1 percent: Absentee debtors and their hedge funds - Stefano Sgambati (City, University of London, City Political Economy Research Centre (CITYPERC), 2024)
The existing literature on finance, debt and inequality depicts economic elites as a creditor class. According to a popular thesis, over the past four decades, the rich and ultra-rich households in the top 1 percent have experienced a saving glut (excess income), which they have invested in the debts of the poor and their governments. While it is undeniable that the rich have expanded their income share at the expenses of the poor, to refer to them as 'creditors' or 'lenders' is a misrepresentation of how they actually expand their wealth and income shares by financial means. For it conceals the fact that a great deal of their investments is leveraged, that is, carried out with borrowed money. This article shows that the debts generated by individuals and households in the top 1 percent easily surpass those of all other households and even exceed those of the most indebted states in the world. However, these debts are hard to estimate, and indeed they are not accounted for in statistics on household debt. This is because households in the top 1 percent do not borrow from banks, like normal households do, but they are instead absentee debtors who borrow through the hedge funds, private equity firms, personal investment trusts, and big banks of which they are dominant shareholders and ultimate beneficiaries. To gain an insight into their invisible leverage, the article looks at how much hedge funds borrow, and why their leverage matters.
Keywords: 330; Elites; Finance; Inequality; Leverage; Hedge Funds